Monitoring and managing queen conch fisheries : - Medley, Paul (Food and Agriculture Organization og the United Nations, 2008)
This publication presents guidelines on the requirements for responsible management of the fisheries exploiting Caribbean queen conch (Strombus gigas), with particular emphasis on the requirements to comply with the relevant regulations of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). The Caribbean queen conch is listed on Appendix II of the CITES, which requires that any specimen of the species can only be exported if a permit has been issued to allow the export. Further, CITES states that export permits should only be issued when the responsible authority has deemed that the export will not be detrimental to the survival of that species. This manual describes the basic fisheries management cycle which includes: development and interpretation of policy; the need for management controls to regulate fishing activities; data collection and analysis; decision-making; enforcement of and compliance with the management controls; and regular feedback and review of the management system. It provides general guidance on each of those steps for the queen conch fisheries of the Caribbean. It also provides three examples of management systems for industrial, artisanal and non-directed fisheries.